2008
DOI: 10.1088/0264-9381/25/20/205022
|View full text |Cite
|
Sign up to set email alerts
|

Fermions tunnelling from the charged dilatonic black holes

Abstract: Kerner and Mann's recent work shows that, for an uncharged and non-rotating black hole, its Hawking temperature can be correctly derived by fermions tunnelling from its horizons. In this paper, our main work is to improve the analysis to deal with charged fermion tunnelling from the general dilatonic black holes, specifically including the charged, spherically symmetric dilatonic black hole, the rotating Einstein-Maxwell-Dilaton-Axion (EMDA) black hole and the rotating Kaluza-Klein (KK) black hole. As a result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 71 publications
4
66
0
Order By: Relevance
“…In the limit when the Gödel parameter is equal to zero ( j = 0) the obtained relation (45) can be represented in the form (31).…”
Section: Tunnelling Of Scalar Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the limit when the Gödel parameter is equal to zero ( j = 0) the obtained relation (45) can be represented in the form (31).…”
Section: Tunnelling Of Scalar Particlesmentioning
confidence: 99%
“…Different aspects of Kaluza-Klein black holes were also considered, namely thermodynamics [39][40][41], Hawking radiation and the tunnelling method [42][43][44][45][46][47][48], quasinormal modes and stabilities [49][50][51][52][53], geodetic precession [54] and gravitational lensing [55].…”
Section: Introductionmentioning
confidence: 99%
“…Impose this operator on the spin network states ψ s . Thus we get 37) where I denotes the edge of the spin networks and j I is a positive half integer. In string theory, we quantize the world sheet in the Ricci flat target space.…”
Section: The Viewpoint Of Loop Quantum Gravitymentioning
confidence: 99%
“…The subsequent work in the virous spacetimes can be found in Refs. [31,32,33,34,35,36,38,37,39,40,41,42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In their seminal work, Kerner and Mann used the Dirac equation instead of the HamiltonJacobi one to obtain the temperature of the emitted fermions and showed that for a chosen type of spacetime the temperature of the emitted fermions would be the same as the temperature of scalar particles [17]. That method was later applied to different kinds of black hole spacetimes, including the Reissner-Nordström one [18], the Kerr-Newman one [19,20], dilatonic black holes [21], BTZ black holes [22], black holes in Hořava-Lifshitz gravity [23,24], accelerating and rotating black holes [25,26], and rotating black strings [27].…”
Section: Introductionmentioning
confidence: 99%